1990
DOI: 10.1007/bf01646857
|View full text |Cite
|
Sign up to set email alerts
|

Einsparung von Diclofenac durch B-Vitamine: Ergebnisse einer randomisierten Doppelblindprüfung mit reduzierten Tagesdosierungen von Diclofenac (75 mg Diclofenac versus 75 mg Diclofenac plus B-Vitamine) bei akuten Lendenwirbelsäulensyndromen

Abstract: Pain syndromes of the lumbar spine are one of the main problems in orthopedic practice. The therapeutic effect of NSAIDs is not subject to doubt in this connection. But considering that the application of NSAIDs is frequently associated with side effects, a reduction of dosage would be to the patient's benefit. Clinical studies have shown that concomitant treatment with vitamins B1, B6, B12 and diclofenac leads to a more efficient pain relief than treatment using diclofenac alone and thus provides the possibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 7 publications
0
6
0
3
Order By: Relevance
“…Die [7,8,40,41,58], oder die Schmerzen mit einer niedrigeren täglichen Dosis von Diclofenac als normalerweise üblich behandelt werden konnten [40,42].…”
Section: Kombinationen Von B-vitaminen Mit Analgetikaunclassified
“…Die [7,8,40,41,58], oder die Schmerzen mit einer niedrigeren täglichen Dosis von Diclofenac als normalerweise üblich behandelt werden konnten [40,42].…”
Section: Kombinationen Von B-vitaminen Mit Analgetikaunclassified
“…The combination of diclofenac with vitamins B 1 , B 6 , and B 12 has been reported to be beneficial in the treatment of painful conditions, including post-operative pain [9], osteoarthritis [10], and especially low back pain. Prior to the publication of the DOLOR trial, encouraging results in clinical studies of low back pain employing the combination of vitamins B 1 , B 6 , and B 12 with diclofenac had been reported in the literature, especially in terms of shortened treatment time to satisfactory analgesia when compared with diclofenac monotherapy [11]- [14]. The results of the DOLOR study confirmed these findings and the results of this post-hoc analysis reinforced the benefit of adding vitamins B 1 , B 6 , and B 12 to diclofenac therapy in terms of shorter treatment time to desired clinical effect.…”
Section: Discussionmentioning
confidence: 99%
“…Reported side effects of DCF include gastrointestinal lesions, headache, dizziness, skin rashes, edema and hepatic and renal damage. B vitamins have been reported to potentiate the antinociceptive and analgesic effects of DCF and several papers have documented their contributions to reduce daily DCF dosage and shorten the treatment time [2][3][4]. Although some studies have questioned the antinociceptive efficacy of B vitamins concomitantly administered with DCF [5,6], these compounds have been commercialised together in a number of formulations in different countries in the last decade.…”
Section: Introductionmentioning
confidence: 97%